Gender-Based Counter-Terrorism Policing: Case Study of Women’s Involvement in ISIS Terrorism Network in Indonesia (International Journal of Scientific Research and Management (IJSRM), 2022)
Since 2016, terrorist networks and acts in Indonesia have made women the executor of terror acts who carry out heinous attacks on targets, even through suicide bombings. This violence is actually manifested by women who are often perceived as gentle, motherly, and far from anarchic actions and act as wives who support the terrors of their husbands. This paper tries to explain the shift in the role and involvement of women in acts of terrorism carried out by the transnational terrorism group ISIS and its networks in Indonesia. This research explores the characteristics of terrorist networks and acts in Indonesia, the cases that occurred, the background of life, and the process of radicalization targeting women. By using a qualitative methodology in the form of case studies and gender concepts with a counter-terrorism approach, this article offers a solution in the form of gender-based counter-terrorism policing as a sharper and more focused approach to preventing acts of terrorism carried out by female terrorists.